Enhancing Accessibility for Inclusive Education: Basis for Faculty Profiling and Facility Enhancement Input - Reyes, Jeniel G (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study explored the potential for promoting inclusive education at the Bataan Peninsula State University – Balanga Campus (BPSU-BC). Methodology: The study employed a convergent parallel design. The researcher gathered both quantitative and qualitative data to assess the awareness and knowledge levels among faculty members regarding campus accessibility in inclusive education. Main Findings: The findings indicate that the faculty members are well informed and sensitive to inclusive education, especially in their willingness to accommodate the students with disabilities, however, in spite of the willingness and the knowledge and awareness of the faculty members, increased institutional support may further enhance inclusive practice within the campus. Likewise, faculty finds the campus to be overall accessible, with signage being given the highest rating, followed by architecture. Though the overall rating is good, the low accessibility of assistive tools for students with disability shows that investment in inclusive tools is still needed. Moreover, the findings indicate that neither the awareness nor the knowledge of the faculty regarding inclusive education are significantly related to campus accessibility to inclusive education. More so, the findings revealed a need for explicit policies that integrated inclusivity into teaching, student activities, and daily campus operations. Faculty training on accommodating students with physical disabilities and mental health conditions was also deemed necessary. Furthermore, facility improvements were suggested to support learners with physical challenges. Novelty/Originality of this study: This study provided recommendations for faculty profiling and facility enhancements, aligning BPSU-BC with national policies for inclusive education.